VARIOUS SPEECH SEQUENCES OF ENGLISH DEPARTMENT STUDENTS IN DOING REQUEST VIA SHORT MESSAGE SERVICE - Ike Revita (Langkawi: Journal of The Association for Arabic and English, 2015)
Interaction, if not wisely considered, may be very risky. The unwise utterances maylead to misunderstanding. When this happens, pragmatic failure is of greatpossibility occur. This writing is aimed at describing the some variations ofspeech seqeunces in doing request and the reasons of using each variation. Thedata are the request uttered by English Department students Andalas Universityto their friends, their lecturer and vice versa at the campus. Data are collected byobservational method, interviewing and note-taking technique. To analyze the data,pragmatic and referential identity method is used. The result of analysis isnaratively and descriptively presented. Having been related to the concept ofspeech act of request (Revita, 2008) and context (Yule, 1986), it is found that thereare four variations of speech sequence when English Department students dorequest. They are (a) (1) 1 in 1; (b) 2 in 1; (c) 3 in 1; and (d) multi acts in 1. Thechoice of these variations is basically based on several reasons, namely (i) social;(ii)psychological; (iii) cultural ; and (iv) religious aspect.Keywords: Sequence, request, short message service